Hot and malignant – a case of invasive papillary carcinoma in hyperthyroid patient with hot nodules. Issue 4 (4th July 2018) - Pandey, Ramesh K.; Sharma, Eliza; Roy, Sasmit; Kandel, Saroj; Dahal, Sumit; Hossain, Muhammad Rajib; Schmidt, Marie F.; Shiferaw-Deribe, Zewge
ABSTRACT: Introduction : Malignant thyroid nodules are clinically euthyroid and appear as cold nodules on scintigraphy. Malignancy in hyper-functioning thyroid nodule is rare. Case report : A 48-year-old male with painless swelling on the right side of his neck for the last 4 months complained of feeling hot all the time, sweating and unintentionally losing about 20 pounds. On physical examination, there was a 3-cm mobile, non-tender mass on the right supra-clavicular area biopsy of which was consistent with metastatic papillary carcinoma of thyroid. Neck imaging showed a cystic mass in the right supra-clavicular fossa region, bilateral neck adenopathy and multiple thyroid nodules. Subsequent thyroid radionuclide scans showed three hyper-functioning nodules, which were later demonstrated to be a follicular variant of papillary microcarcinoma. He was treated with total thyroidectomy followed by radioactive iodine thyroid ablation therapy. Conclusion : Physicians need to be aware and vigilant for the possibilities of malignancy in a hyper-functioning thyroid nodule when evaluating any thyroid nodule.